2020
DOI: 10.1111/acps.13219
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression in the Republic of Ireland during the COVID‐19 pandemic

Abstract: Background The COVID‐19 pandemic in Ireland resulted in a nationwide quarantine on March 27, 2020. This study represents the first assessment of rates of anxiety and depression in the general population of Ireland during the pandemic. Aims Our first aim was to estimate the probable prevalence rates of generalized anxiety disorder (GAD) and depression and to identify sociodemographic risk factors associated with screening positive for GAD or depression. Our second aim was to determine if COVID‐19 related anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

54
332
12
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 478 publications
(470 citation statements)
references
References 20 publications
54
332
12
14
Order By: Relevance
“…Similar recruitment strategies and measures have been used by international collaborators in other countries, including Ireland, 10 Italy, Spain, Saudi Arabia and the United Arab Emirates.…”
Section: Covid-19-related Anxietymentioning
confidence: 99%
“…Similar recruitment strategies and measures have been used by international collaborators in other countries, including Ireland, 10 Italy, Spain, Saudi Arabia and the United Arab Emirates.…”
Section: Covid-19-related Anxietymentioning
confidence: 99%
“…8 Here we report initial findings from the first wave of a longitudinal, multi-wave survey of the social and psychological impacts of COVID-19 on the UK population conducted by researchers in seven UK and Irish universities (the Covid-19 Psychological Research Consortium; C19PRC) 9 . Of note, in a mirror study with similar methodology, we recently reported the social and psychological impacts of COVID-19 on the Republic of Ireland population 10 . The primary aim of this paper is to assess the levels of anxiety, depression and traumatic stress, based on validated self-report measures, in a large, representative community sample during an early stage of the pandemic, between March 23 rd and March 28 th , 2020.…”
mentioning
confidence: 99%
“…Based on scant previous studies 11 2 and given the dramatic restrictions imposed because of COVID-19, we expected higher levels of common psychological and stress symptoms compared with previous population estimates. Our secondary aim was to identify groups that are psychologically vulnerable during the pandemic, by assessing the relationship between levels of anxiety, depression and traumatic stress and (1) age; (2) household income; (3) economic threat due to COVID-19; (4) health related risk factors (being male, self or close friend/relative having pre-existing serious health condition), (5) COVID-19 infection status, (6) anxiety specifically related to COVID-19, (7) perceived risk of COVID-19 infection, (8) living in an urban area, (9) living as a lone adult and (10) living with children in the home.…”
mentioning
confidence: 99%
“…The media has reported countless anecdotes of anxiety, depression, [1][2][3][4] and domestic violence, [5][6][7] while scienti c journals have published numerous case reports and clinical studies from all over the world. [8][9][10] As of July 29, 2020, a simple PubMed search of "covid 19…”
Section: Introductionmentioning
confidence: 99%